Examining Posttraumatic Growth Among Turkish Family Caregivers of Cancer Patients - Guven, Serkan; Topkaya, Nursel; Sahin, Ertugrul; Aras, Nur Yagmur (Nature Portfolio, 2024)
Cancer is a deadly disease that affects millions of people worldwide and is a source of great difficulty, stress, and trauma not only for patients but also for their caregivers. The physical and emotional suffering that patients experience by patients can lead their caregivers to cope with constant anxiety, sadness, and uncertainty. Moreover, during the cancer treatment process, caregivers must make a great effort to meet the needs of patients and support them. This situation may negatively affect the quality of life and psychological health of cancer patients' caregivers and may lead them to experience trauma. The aim of this cross-sectional study was to examine posttraumatic growth's relationship with age, the transformative power of suffering, and hope in family caregivers of cancer patients. Participants consisted of 314 Turkish family caregivers of cancer patients (73.2% women; Mage = 39.89 years) selected by using convenience sampling method. Participants answered a data collection tool consisting of a demographic information form, the Posttraumatic Growth Inventory, Trait Hope Scale, and Transformative Power of Suffering Scale. Data were analyzed using descriptive statistics, the Pearson product-moment correlation coefficient analysis, simple mediation analysis, and moderated mediation analysis. The results of this study revealed that hope mediated the association between the transformative power of suffering and posttraumatic growth in family caregivers of cancer patients, whereas age moderated this relationship. Psychosocial support programs for cancer caregivers could benefit from incorporating interventions that explore the transformative potential of suffering and cultivate hope. Tailoring these interventions to address the specific needs of different age groups may enhance their effectiveness. Future researchers should investigate the factors associated with posttraumatic growth in caregivers across diverse cultures, age ranges, and cancer diagnoses.
Güven, Serkan/0000-0001-8933-1081; Şahin, Ertuğrul/0000-0003-3341-8887
Keywords: Family Members of Cancer Patients; Posttraumatic Growth; Age; Transformative Power of Suffering; Hope